Why bureaucracies matter in the global age: A post-Weberian explanation with the case study of preparing and implementing the United Nations' An Agenda for Peace. (March 2014) - Kanninen, Tapio; Piiparinen, Touko
This article will challenge the conventional wisdom according to which international bureaucracies are unviable and undesirable in the age of globalisation. The relevance and powers of today's international bureaucracies can best be understood by reference to the model of the 'network logic of globalisation' rather than Max Weber's classic theory alone. Bureaucracies are undergoing a transformation from the rigid and hierarchical institutions of Weber's time to more network-oriented and delayered post-Weberian entities. On occasion, these post-Weberian structures allow middle-level officials in international organisations to wield considerable new bureaucratic powers. The case study of this article draws upon empirical evidence on the drafting and implementation of An Agenda for Peace (1992) by UN Secretariat officials and its contributions to the United Nations early warning and conflict prevention mechanism. The network-oriented structures and approaches have started to permeate the UN Organisation in two ways: First, the United Nations operates more and more through interdepartmental and interagency teams. This trend was evident already in the drafting and implementation processes of the Agenda. Second, the United Nations is reaching out to academic and civil society networks. The start of these two transformations of the UN bureaucracy is related to globalisation and can be seen already in action in the early 1990s when the Agenda was drafted.